A clinical comparison between nickel titanium springs and elastomeric chains - Bokas Jim; Woods Michael (Sciendo, 2023)
To compare the rates of maxillary canine retraction and molar anchorage loss when using either NiTi springs or elastomeric chains delivering a known force with sliding edgewise mechanics.